Aquarium Tank Design Is Integral to the Elimination of Mantle Abrasion in the Captive Curled Octopus (Eledone cirrhosa): A Case Study at Macduff Marine Aquarium. Issue 4 (2nd October 2022) - Smith, Lauren E.; Rowe, Christopher; Mackay, Frazer; Matthews, Claire; Matthews, Christopher G. G.
ABSTRACT: Macduff Marine Aquarium is a native species aquarium situated on the Moray Firth coastline and houses the curled octopus, Eledone cirrhosa, for public display. Historically, the designated octopus display tank has been in-keeping with the overall theme of the aquarium, consisting of artificially created rock work mimicking the local rocky coastline, within an angular glass tank. This tank was not originally designed for housing octopus and as a consequence, if individuals on display exhibited jetting behavior mantle abrasion occurred. In 2016, a new bespoke octopus tank was designed and installed. Since then 14 different octopuses have been individually housed and maintained within the tank, with none having experienced mantle abrasion. This paper highlights the importance of aquarium design for the ethical maintenance of an intelligent and challenging species.